Pengaruh Volume Kendaraan Terhadap Tingkat Kerusakan Jalan di Daerah Lamreung - Wati, Yusra; Pramanda, Heru; Kamalia, Kamalia; Mubarak, Azzaki; Muhajjir, Muhajjir (Universitas Iskandar Muda, 2025)
This study aims to analyze the influence of traffic volume on road damage levels and identify the causes of deterioration along the Cor Iri–Lamreung segment in Aceh Besar District. The research also provides relevant information for planning road construction and maintenance, including determining appropriate material types for road structures. A quantitative data analysis approach was employed, using the Indonesian Highway Capacity Manual (PKJI) 2023 and the Bina Marga method to assess physical road conditions. The results on the Tgk. Nyak Arief road section show that the most dominant type of damage is potholes, accounting for 18.0%, while the total damage percentage (Nr) reached 59.2%. Traffic volume surveys conducted over three days (26–28 May 2025) indicate that the highest Average Daily Traffic occurred on Monday, with an average capacity of 677 pcu/hour. Motorcycle volume remained consistently high, especially in the morning. Based on the priority index, the road section obtained a value of 6, indicating that it should be included in a routine maintenance program. Overall, the combination of PKJI 2023 and Bina Marga methods provides a comprehensive analysis of the relationship between traffic volume and road deterioration. Higher traffic volumes, particularly from heavy vehicles, significantly increase damage levels. Therefore, proper traffic load management and planned maintenance programs are required to maintain road performance. These findings serve as recommendations for authorities to improve attention to construction materials and design quality to ensure road durability amid increasing traffic demand.